Kinetika Absorpsi CO₂ dari Gas Buang Kendaraan dengan Menggunakan Absorben KOH pada Reaktor Gelembung Pancaran - Sirait, Agnes Tasya Pintauly; Muhammad Yerizam; Akbar Ismi Aziz Pramito (Jurnal Serambi Engineering, 2025)
This research aims to find out the kinetics of CO₂ absorption reaction of automobile exhaust gas using potassium hydroxide (KOH) as an absorbent in a jet bubble reactor. The jet bubble reactor was chosen because of its ability to increase the contact area between gas and liquid, thereby increasing the absorption efficiency. The variables analyzed in this study include KOH concentration, gas flow rate, and operating temperature. A study was conducted on CO₂ gas absorption in automotive gas using pure KOH alkali base solution and maximizing absorption in CO₂ exhaust gas. This study was conducted using concentration variations. (0.1, 0.2, 0.3 and 0.4 M), which is an important step to reduce the greenhouse effect that will negatively affect the environment.